2004
DOI: 10.4161/cc.3.2.667
|View full text |Cite
|
Sign up to set email alerts
|

Flavopiridol inhibits the Growth of GL261 Gliomas In Vivo: Implications for Malignant Glioma Therapy

Abstract: The mechanism of action of many chemotherapeutic agents targets the cell cycle. Recently, we demonstrated cytotoxic and other anti-tumor effects of flavopiridol, the first synthetic cyclin dependent kinase (CDK) inhibitor to enter clinical trials, on the murine GL261 glioma cell line in vitro (Newcomb et al., Cell Cycle 2003; 2:243). Given that flavopiridol has demonstrated anti-tumor activity in several human xenograft models, we wanted to evaluate it for anti-glioma activity in vivo in our established subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 18 publications
1
41
0
1
Order By: Relevance
“…36,37 In addition to its ability to kill cells in S phase, flavopiridol also can recruit cells into the S phase when it is delivered 48 or 72 h apart. 11,32 Our results demonstrate that the schedules chosen for radiation and flavopiridol treatments produced a highly significant delay in tumor growth. Since noncycling cells are relatively radio-resistant, the enhanced radiosensitizing effects of flavopiridol observed in this study of repeated doses of both radiation and flavopiridol treatments can be hypothesized to be due, at least in part, to its ability to affect tumor repopulation.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…36,37 In addition to its ability to kill cells in S phase, flavopiridol also can recruit cells into the S phase when it is delivered 48 or 72 h apart. 11,32 Our results demonstrate that the schedules chosen for radiation and flavopiridol treatments produced a highly significant delay in tumor growth. Since noncycling cells are relatively radio-resistant, the enhanced radiosensitizing effects of flavopiridol observed in this study of repeated doses of both radiation and flavopiridol treatments can be hypothesized to be due, at least in part, to its ability to affect tumor repopulation.…”
Section: Discussionmentioning
confidence: 68%
“…We and others have shown that flavopiridol is an S-phase specific drug. 11,[33][34][35] We elected to give fractionated radiation in a protracted schedule of 5 fractions of 5 Gy delivered over ten days in order to test our hypothesis that flavopiridol would selectively kill proliferating cells in S phase, by overcoming repopulation of tumor cells between fractionated radiation treatments. 36,37 In addition to its ability to kill cells in S phase, flavopiridol also can recruit cells into the S phase when it is delivered 48 or 72 h apart.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations